Development of Physics Comics Based on Guided Inquiry Model Assisted by Social Media to Increase Students' Interest in Learning - Fijira Pasyah; Ardian Asyhari; Happy Komikesari (Mataram University, 2026)
This study aims to develop a physics comic based on a guided inquiry model and using social media to increase students' interest in learning Newton's Laws. In the context of physics learning, which tends to be considered difficult and boring, this study focuses on exploring comics as a more engaging and effective medium for increasing student engagement. The research design used was an experiment with an experimental group consisting of 40 students from two high schools in Indonesia. The sampling technique used was purposive sampling, with students selected who had adequate internet access. Data were collected through pretests and posttests to measure changes in students' learning interest, as well as questionnaires to assess students' responses to the learning media. The data analysis technique used was a paired t-test to identify differences between pretest and posttest scores. The results showed that the use of a physics comic based on a guided inquiry model using social media had a significant effect on increasing student motivation and engagement in physics learning. These findings provide a practical contribution to the development of more innovative and engaging learning media, and enrich the literature on the use of comics and social media in physics education. Theoretically, this study strengthens the constructivism and social learning frameworks in the context of physics learning.